Sequence analysis of bla CTX-M-28 , an ESBL responsible for third-generation cephalosporin resistance in Enterobacteriaceae, for the first time in India - Kingsley Jemima; Verghese Susan (Wolters Kluwer Medknow Publications, 2008)
The most common group of ESBLs not belonging to the bla TEM or bla SHV families were termed bla CTX-M , to highlight their ESBLs′ greater activity against cefotaxime than against ceftazidime. The presence of nosocomial bla CTX-M-28 -producing Enterobacteriaceae strains has not been reported earlier in Indian hospitals. The sequences of bla CTX-M-28 gene from cephalosporin-resistant Enterobacteriaceae were analyzed. The structural gene encodes a 290 amino-acid protein, which is most related to the bla CTX-M β-lactamases. The conserved K-T-G was identified in the bla CTX-M-28 protein sequence, but significantly, two point mutations (N→T) and (F→S) were identified in the Y-G-N- and S-T-F-K-conserved motifs respectively. These point mutations were seen in all the three sequenced isolates